2018
DOI: 10.12701/yujm.2018.35.2.192
|View full text |Cite
|
Sign up to set email alerts
|

Antiepileptic and anti-neuroinflammatory effects of red ginseng in an intrahippocampal kainic acid model of temporal lobe epilepsy demonstrated by electroencephalography

Abstract: Background: Chronic inflammation can lower the seizure threshold and have influence on epileptogenesis. The components of red ginseng (RG) have anti-inflammatory effects. The abundance of peripherally derived immune cells in resected epileptic tissue suggests that the immune system is a potential target for anti-epileptogenic therapies. The present study used continuous electroencephalography (EEG) to evaluate the therapeutic efficacy of RG in intrahippocampal kainic acid (IHKA) animal model of temporal lobe e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 17 publications
1
9
2
Order By: Relevance
“…We provide evidence of prolonged convulsive seizures similar to seizure durations reported in human TLE (Balish et al, 1991) and data from an Epilepsy Monitoring Unit (Jenssen et al, 2006). The longer-lasting seizures contrast with the 3-7 sec epileptiform abnormalities reported by some past studies of IHKA in mice (Kim et al, 2018; Sandau et al, 2019; Lai et al, 2020). In addition, our results differ from what appears to be continuous spiking at the site of IHKA injection indicated by some investigators (Sandau et al, 2019).…”
Section: Discussioncontrasting
confidence: 77%
See 3 more Smart Citations
“…We provide evidence of prolonged convulsive seizures similar to seizure durations reported in human TLE (Balish et al, 1991) and data from an Epilepsy Monitoring Unit (Jenssen et al, 2006). The longer-lasting seizures contrast with the 3-7 sec epileptiform abnormalities reported by some past studies of IHKA in mice (Kim et al, 2018; Sandau et al, 2019; Lai et al, 2020). In addition, our results differ from what appears to be continuous spiking at the site of IHKA injection indicated by some investigators (Sandau et al, 2019).…”
Section: Discussioncontrasting
confidence: 77%
“…A study in the pilocarpine model suggested that single housing may increase seizures by a factor of 16 (Manouze et al, 2019). Single housing might thus explain why very frequent and brief (3-7 sec) epileptiform abnormalities have been reported in IHKA-treated mice in the past (Kim et al, 2018; Sandau et al, 2019; Lai et al, 2020; Rusina et al, 2021). It would be possible that our approach that included frequent handling combined with enriched housing reduced these very frequent abnormalities thereby allowing the expression of robust seizures.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…EEG recordings from the site of IHKA injection showed that most frequent epileptiform abnormalities in mice were short-lasting non-convulsive episodes ( Bouilleret et al, 1999 ; Maroso et al, 2011 ) which are not compelling seizures. Brief (3–7 s) abnormalities were reported by others where they could be as frequent as 100 per hr ( Kim et al, 2018 ; Sandau et al, 2019 ; Lai et al, 2020 ) which are also inconsistent with characteristics of seizures from an epileptic animal. Sometimes the EEG examples that were published suggested trains of spikes or epileptiform activity occurred in the wks after IHKA, but these are not clear seizures.…”
Section: Introductionmentioning
confidence: 83%